Pengaruh Lingkungan Kerja Terhadap Semangat Kerja Perangkat Desa di Desa Suci Kecamatan Karangpawitan Kabupaten Garut - Rifayani, Helena Pelly; Candradewini, Candradewini (PREDIKSI : Jurnal Administrasi dan Kebijakan, 2024)
As providers of public services, village officials must possess high work morale, with the work environment being a significant factor contributing to its enhancement. Observable issues related to work morale include elevated absenteeism, recurrent tardiness, and the preference to complete tasks at home due to disturbances in concentration caused by noise at the Village Office. Initial observations indicate a need to enhance management associated with the work environment at the Suci Village Office. This research aims to elucidate the extent of the impact the work environment has on the work spirit of village officials at the Suci Village Office, Karangpawitan District, Garut Regency, using quantitative research methods. The correlation coefficient (R) test results reveal a robust and positive correlation of 74.9% between the work environment and work morale. The R Square value of 0.560 indicates that 56% the work morale variable can be influenced by the work environment, while the remaining 44% is influenced by unexplored variables. This underscores that effective management and an improved work environment can significantly boost the work spirit of village officials at the Suci Village Office, Karangpawitan District, Garut Regency.